Neuromyelitis Optica Spectrum Disorders. Issue 4 (August 2022) - Costello, Fiona
ABSTRACT: PURPOSE OF REVIEW: This article reviews the cardinal clinical features, distinct immunopathology, current diagnostic criteria, relapse-related risk factors, emerging biomarkers, and evolving treatment strategies pertaining to neuromyelitis optica spectrum disorders (NMOSD). RECENT FINDINGS: The discovery of the pathogenic aquaporin-4 (AQP4)-IgG autoantibody and characterization of NMOSD as an autoimmune astrocytopathy have spearheaded the identification of key immunologic therapeutic targets in this disease, including but not limited to the complement system, the interleukin 6 (IL-6) receptor, and B cells. Accordingly, four recent randomized controlled trials have demonstrated the efficacy of three new NMOSD therapies, namely eculizumab, satralizumab, and inebilizumab. SUMMARY: Currently, NMOSD poses both diagnostic and treatment challenges. It is debated whether individuals who are seropositive for myelin oligodendrocyte glycoprotein (MOG)-IgG belong within the neuromyelitis optica spectrum. This discussion is fueled by disparities in treatment responses between patients who are AQP4-IgG seropositive and seronegative, suggesting different immunopathologic mechanisms may govern these conditions. As our understanding regarding the immune pathophysiology of NMOSD expands, emerging biomarkers, including serum neurofilament light chain and glial fibrillary acidic protein (GFAP), may facilitate earlier relapse detection and inform long-term treatment decisions. Future research focal points should include strategies to optimize relapse management, restorative treatments that augment neurologic recovery, and practical solutions that promote equitable access to approved therapies for all patients with NMOSD.